Availability Level of Digital Citizenship in the Computer and Information Technology Book for the Third Grade of the Intermediate Stage in the Kingdom of Saudi Arabia - Aloufi, Hanan Suwayid; Alzahrani, Majed Gharmallah (Journal of Educational and Psychological Sciences, 2021)
This study aimed to know the availability level of the elements of digital citizenship in the content of computer and information technology book for the third grade of the intermediate stage in Kingdom of Saudi Arabia. The study followed the descriptive methodology represented by the content analysis method, and the sample of the study was the computer and information technology book for the third stage in intermediate school and a form of content analysis was used for collecting data after ascertaining its validity and reliability. The study found the availability of (15) indicators out of (63) indicators within the elements of digital citizenship and a total of (358) frequencies, which indicates to the poor availability of the elements of digital citizenship in the content of the book, as the digital culture element had the highest percentage of availability among the nine elements (83.79%), and the rest of the elements of digital citizenship received very low percentages of availability and distributed varyingly which did not exceed (9%), while the element of digital health and safety, and the element of digital rights and responsibilities were not available entirely. The study recommended that the elements of digital citizenship should be included in the content of computer and information technology book for the third intermediate stage for the intermediate stage to be used towards the benefits of digital technologies and avoid their danger and educating computer teachers about it.